1994
DOI: 10.1093/schbul/20.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tracking and Schizophrenia: A Selective Review

Abstract: The replications of the finding of eye tracking dysfunction (ETD) in schizophrenia patients and their first-degree relatives suggest that ETD may be informative in studies of a schizophrenia genotype having broadly defined phenotypes. We review and critically assess the literature on ETD with respect to syndrome and familial specificity and discuss the quantitative assessment of eye tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(56 citation statements)
references
References 98 publications
1
54
0
1
Order By: Relevance
“…Interestingly, individuals with schizophrenia have long been recognized to exhibit a variety of disturbances in motor control. For example, numerous studies have demonstrated that schizophrenic subjects display abnormalities in smooth pursuit eye movements (Holzman et al 1973;Hutton and Kennard 1998;Levy et al 1994). The fastigial nucleus, the principal target of efferents from the cerebellar vermis (Ito 1984), is activated during pursuit eye movements (Fuchs et al 1993;Vilis and Hore 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, individuals with schizophrenia have long been recognized to exhibit a variety of disturbances in motor control. For example, numerous studies have demonstrated that schizophrenic subjects display abnormalities in smooth pursuit eye movements (Holzman et al 1973;Hutton and Kennard 1998;Levy et al 1994). The fastigial nucleus, the principal target of efferents from the cerebellar vermis (Ito 1984), is activated during pursuit eye movements (Fuchs et al 1993;Vilis and Hore 1981).…”
Section: Discussionmentioning
confidence: 99%
“…For example, many subjects with schizophrenia exhibit abnormalities in smooth pursuit eye movements (Holzman et al 1973;Levy et al 1994;Hutton and Kennard 1998). In addition, some of the cognitive deficits observed in individuals with schizophrenia, such as impairments in planning, verbal fluency, abstract thinking, and working memory, are present in patients with cerebellar lesions (Schmahmann and Sherman 1998).…”
Section: The Cerebellum Seems To Play a Critical Role In Many Motor Amentioning
confidence: 99%
“…Schizophrenia has been associated with abnormalities of smooth pursuit (Levy et al 1994) and more recently increased antisaccadic errors, which are erroneous reflexive saccades made towards a peripheral target when subjects are instructed to direct their gaze to its mirror image location (Crawford et al 1995;Fukushima et al 1990;Katsanis et al 1997;McDowell & Clementz, 1997). Both abnormal smooth pursuit and increased antisaccade errors have been found at illness onset in medication-naĂŻve patients (Sweeney at al, 1992;Lieberman et al 1993;Hutton et al 1998) and in first-degree relatives (Holzman et al 1988;Crawford et al 1998;Ross et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A physiologic measure that has received attention in HR studies is eye tracking abnormality [54], which is seen in approximately 50% of adult relatives; studies of smooth pursuit eye movements in adolescent HR subjects have shown significant dysfunction compared with healthy comparison subjects [55]. Eye movement studies have shown lack of age related improvements in oculomotor delayed response performance in young HR subjects [56].…”
Section: Electrophysiologic Studiesmentioning
confidence: 99%